Leaching in reactive froth of zinc sulphide concentrate - Obeng, Daniel Philip (My University, 1997)
Laboratory experimentation were conducted to investigate the regeneration and recycling of nitric acid during leaching in froth (LIF) processing of Gamsberg zinc sulphide concentrate. Two experiments were performed in a mechanically stirred batch reactor at 80- 90°C to determine the leaching kinetics of the zinc sulphide concentrate. 93 to 97% of zinc was extracted into spent zinc sulphate electrolyte containing 30 to 40g/1 nitric acid during 40 to 60 minutes of leaching without regeneration of nitric acid. Between 60.72. and 97.79% of the consumed nitric acid was regenerated after 45 minutes of batch L/F experiments carried out at 80·90oC and 50kPa. The results show that the degree of nitric acid regeneration is inversely proportional to the concentration of nitric acid in the leaching solution. Zinc extraction ranged between 56.31 and 78.37% whilst 40.29 to 50.99% of the initial sulphide sulphur was oxidised to elemental sulphur. In the continuous L/F experiments conducted at 80- 90°C and 100·200kPa, the degree of nitric acid regeneration varied from 33.63 to 97.22%. Overall zinc extraction was about 62% whilst 47% of the sulphide sulphur reported as elemental sulphur after 60 minutes of processing. A five-stage L/F processing of the concentrate was carried out in which the flotation phenomenon was used for selective separation of the floatable fraction from the nonfloatable fraction. About 40 to 80% of the consumed nitric acid was regenerated, 88.94% of zinc was extracted whilst 55.65% of the sulphide sulphur reported is elemental sulphur after 77 minutes of processing. The recoveries of zinc and elemental sulphur increased to over 92% and 58% respectively when the leach residue was subsequently leached in the batch reactor.
A dissertation submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Master of Science in Engineering.
Keywords: Zinc -- Metallurgy; Leaching